PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL PADA NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Kadek Dewi Padnyawati; Ni Putu Ayu Kusumawati (Jurnal Widya Akuntansi dan Keuangan, 2019)
The purpose of this study was to determine the effect of managerial ownership structure on firm value with dividend policy as an intervening variable (case study on manufacturing companies on the IDX for the period 2014-2016). The number of samples taken was 42 manufacturing companies. Data collection is done through non-participant observation. Multiple regression analysis techniques and path analysis. Based on the results of the analysis it was found that the managerial ownership structure had a positive and significant effect on firm value. Managerial ownership structure has a positive and significant effect on dividend policy. Dividend policy has a positive and significant effect on firm value. This result supports Signaling theory, that dividend payments are a signal to the market, so dividend payments can increase market appreciation for the company's shares. Then there is an indirect effect of managerial ownership structure on the value of company with dividend policy as an intervening variable. This proves that dividend policy is an intervening variable that connects managerial ownership structure with firm value.